Women's and communities' views of targeted educational interventions to reduce unnecessary caesarean section: a qualitative evidence synthesis - Carol Kingdon; Soo Downe; Ana Pilar Betran (BMC, 2018)
Abstract Background There is continued debate about the role of women and communities in influencing rising rates of caesarean section (CS). In settings where CS rates exceed recommended levels, mothers and babies are exposed to potential harms that may outweigh the potential benefits. There is therefore a need to understand how educational interventions targeted at women and communities to reduce unnecessary CS are perceived and used. This qualitative evidence synthesis aimed to explore what women and communities say about the barriers and facilitators to intervention effectiveness for these important groups. Method Seven electronic databases were searched using predefined search terms. Studies reporting qualitative data pertaining to interventions, published between 1985 and March 2017, with no language restriction were sought. Study quality was independently assessed by two authors before qualitative evidence synthesis was undertaken using an interpretive, meta-ethnography approach. Resulting Statements of Findings were assessed using GRADE-CERQual, and summarised thematically. Results Twelve studies were included. They were published between 2001 and 2016. Eleven were from high-income countries. Twelve Summaries of Findings encompassed the data, and were graded (moderate or high) on CerQual. The Statements of Findings are reported under three final themes: 1) Mutability of women's and communities' beliefs about birth; 2) Multiplicity of individual information needs about birth; 3) Interactions with health professionals and influence of healthcare system on actual birth method. Women and communities value educational interventions that include opportunities for dialogue, are individualised (including acknowledgement of previous birth experiences), and are consistent with available clinical care and the advice of the health professional they come into contact with. Conclusion Women's values and preferences for birth, and for information format and content, vary across populations, and evolves in individual women over time. Interactions with health professionals and health system factors can partly be responsible for changes in views. Educational interventions should take into account these dynamic interactions, as well as the women's need for emotional support and dialogue with professionals alongside information about birth. Further research is required to test these findings and the utility of their practical application, particularly in medium and low income settings. Systematic review registration number PROSPERO 2017 CRD42017059453.